The Influence of Information Technology and Monitoring Systems on the Quality of Financial Reports at Bapenda Sumedang Regency - Nurachman, Maman; Yuniawati, Ayi Srie; Fadila, Sarah Nur (LPPM Universitas Sebelas April, 2025)
The term